Poemat Macieja Stryjkowskiego Przesławnego wjazdu do Krakowa i pamięci godnej koronacyjej Henryka Walezyjusa […] opisanie jako relacja poetycka uroczystości. Wartości źródłowe i artystyczne tej wypowiedzi z obszaru okolicznościowej poezji politycznej - Maria Wichowa (Meluzyna: dawna literatura i kultura)
Maciej Stryjkowski’s poem, “The Famous Entry into Krakow and the Worthy Memory of the Coronation of Henry Walezy” is described as a poetic account of the solemn event. The article analyzes the source and artistic values of this expression within the realm of occasional political poetry. The author points out that the evaluation of Stryjkowski’s work by a cursory reading, as done by Juliusz Nowak-Dłużewski, did not withstand the test of time. It is demonstrated that, contrary to the researcher’s characterization as a literary prank, the poem is a mature artistic composition. The poet deliberately chose the descriptive form, consistently applying it in coexistence with narration, discreetly employing numerous rhetorical devices, always with deliberate selection. Stryjkowski demonstrated an excellent knowledge of ancient literature, skillfully adhered to the imperative of imitatio antiquorum, and presented himself as a mature, talented poet, and historian. In line with the fashion of the era, he introduced theatricality into his verbal expression. The merits of the poem were acknowledged by Stryjkowski’s contemporaries, as the work proved worthy of publication shortly after its completion in 1574, likely before Henry Walezy’s departure from Poland.